ANALYZING STUDENT’S SCIENCE LITERACY AND CONTENT ASPECT OF INTERACTION OF ORGANISMS AND ITS ENVIRONMENT TOPIC AT SEKOLAH INDONESIA KUALA LUMPUR - Amaira Utami (Jurnal Biogenerasi, 2022)
The purpose of this study is to capture student’s science literacy and content aspect of interaction of organisms and its environment topic at Sekolah Indonesia Kuala Lumpur. The method of this study is quasi experiment pretest-posttest one group only. The research subject is 7th graders in Sekolah Indonesia Kuala Lumpur. Student’s science literacy on knowledge aspect is captured through 20 multiple choice questions and questionnaire about science learning. The research data is analyzed by the result of normalized gain and its effect size. There are two aspects of science literacy which are measures namely content and procedural knowledge which enhance satisfactory of n-gain 0.52 and 0.75 respectively. The effect size of those two aspects reach 1.24 which means it has strong effect. Moreover, students mostly excel on both abiotic and ecological pyramid subtopic that are correctly answered by 64.77% students. To sum up, student’s science literacy shows satisfactory results and it can be concluded that students can comprehend the topic well.